Cooperating Teachers’ Best Practices for Mentoring #5: Implementation and Adoption of a Cooperating Teacher Preparation and Support Program - Heather R. Nesbitt; Debra M. Barry (EDIS)
This final article in the Best Practices for Mentoring series provides school-based agricultural education programs (SBAE) university faculty and others who serve as program coordinators of the student teaching internship experience with a step-by-step guideline on implementing a cooperating teacher preparation and support program. Written by Heather R. Nesbitt and Debra M. Barry, and published by the UF/IFAS Department of Agricultural Education and Communication, February 2025.